The INCU as a tool for capacity building - Fonseca Ordoñez, Jhon (2008)
This paper examines and furthers theories, concepts and trends in the development of skills as a starting point for capacity building. It aims to identify and develop the most relevant criteria of a ‘network society’, stressing the importance of incorporating this concept in the framework of the INCU which can thereby function as a tool for adequate capacity building on the basis of regional standards predefined by the nations involved. The paper provides a systematic analysis of the main points raised in the ‘Tuning Educational Structures in Europe’ (Tuning Project). That project is widely regarded as representing the major axis of a common educational approach in the European Union (EU). It is argued that the Tuning Project contains some interesting elements that could be used to enhance the PICARD Standards in the future.